Aplikasi Pengembalian Buku Mandiri Menggunakan Segmentasi Citra Cover Buku - Andy Ardianto; Anjik Sukmaaji; Teguh Sutanto (Jurnal Sistem Informasi Universitas Dinamika, 2014)
Library is one of the information center , a source of knowledge and research . Library resources into place so that it can be enjoyed by many people . In a library has several processes performed one of the process is the process of returning books . In the book return process is happening right now in general are using barcode technology, barcode using the technique to facilitate the inventory record books that are in the library. At this time the library has a limited operating hours , with limited operating hours of the library can inhibit the process of returning books during the operating hours of the library was closed . to overcome these problems the need for application of automatic book return . By using the automatic book return the application process of the return of the book can be done without having to see the operating hours of the library . In the automatic book return applications can take advantage of the technological innovation that is image processing . One method of image processing is segmentation , segmentation using the technology of the book cover objects within an image can be distinguished anatara with each other .